Notable dysthymia: evolving trends of major depressive disorders and dysthymia in China from 1990 to 2019, and projections until 2030 - Wei Wang; Yihe Wang; Feng Wang; Hui Chen; Xiaqing Qin; Lexia Yang; Xiaorong Yang; Lejin Yang (BMC, 2024)
Abstract Background Depressive disorders have been identified as a significant contributor to non-fatal health loss in China. Among the various subtypes of depressive disorders, dysthymia is gaining attention due to its similarity in clinical severity and disability to major depressive disorders (MDD). However, national epidemiological data on the burden of disease and risk factors of MDD and dysthymia in China are scarce. Methods This study aimed to evaluate and compare the incidence, prevalence, and disability-adjusted life-years (DALYs) caused by MDD and dysthymia in China between 1990 and 2019. The temporal trends of the depressive disorder burden were evaluated using the average annual percentage change. The comparative risk assessment framework was used to estimate the proportion of DALYs attributed to risk factors, and a Bayesian age-period-cohort model was applied to project the burden of depressive disorders. Results From 1990 to 2019, the overall age-standardized estimates of dysthymia in China remained stable, while MDD showed a decreasing trend. Since 2006, the raw prevalence of dysthymia exceeded that of MDD for the first time, and increased alternately with MDD in recent years. Moreover, while the prevalence and burden of MDD decreased in younger age groups, it increased in the aged population. In contrast, the prevalence and burden of dysthymia remained stable across different ages. In females, 11.34% of the DALYs attributable to depressive disorders in 2019 in China were caused by intimate partner violence, which has increasingly become prominent among older women. From 2020 to 2030, the age-standardized incidence, prevalence, and DALYs of dysthymia in China are projected to remain stable, while MDD is expected to continue declining. Conclusions To reduce the burden of depressive disorders in China, more attention and targeted strategies are needed for dysthymia. It's also urgent to control potential risk factors like intimate partner violence and develop intervention strategies for older women. These efforts are crucial for improving mental health outcomes in China.